Hukum Kepemimpinan Wanita: Perspektif Ulama - Muhajir Muhajir; Fakhrurrazi Fakhrurrazi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2020)
The purpose of this study was to determine the law of female leadership according to the perspective of the Langsa City Ulama in the local elections for the mayor and to identify the factors that influence the different views of the Langsa City Ulama about female leadership in the Langsa City. The method used in this study is a qualitative descriptive research method that produces data in the form of written and spoken words from the subject under study. The main target of this research is the ulama of Langsa city. Data collection techniques are by observation, in-depth interviews and documentation. The data validity used is data triangulation technique. Data analysis includes 4 things, namely data collection, data reduction, data presentation, and concluding. The result of this research is that the ulama of Langsa city show that women can be leaders in the public sector, but the concept of understanding ideal leadership in Islamic teachings that they understand places men as the top priority to become leaders. Women are deemed to be allowed to become leaders if there are no men who can hold the position or the woman has more talent or expertise than the existing men.